USAHA BUDIDAYA DAN PENGOLAHAN ANEKA KULINER JAGUNG DI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Edison; Dharia Renate (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract: There have been various efforts made by corn farmers in improving their competitiveness and the ability to market their corn. It turns out that by turning their cultivated corn into corn culinary, the selling value of corn has improved, but in terms of technical processing, the target audience has not been able to work on corn-based culinary products. The corn processing method is relatively simple, because they are familiar with such tools as cauldrons, blenders and so on. The implementation of service is useful so that: (a) the target audience gains expertise on how to treat good harvests, (b) understands good corn culinary processing, (c) is skilled at making corn culinary. Likewise, service is intended to obtain benefits such as: (a) to improve post-harvest knowledge of corn in order to get the best product, (b) seek activities in the agro-industrial sector so that it can help get